Connecting Policy With Practice: How the Dutch Ministry of Sport Builds Inclusive and Sustainable Communities (Baltic Journal of Sport and Health Sciences, 2026)
To address the challenges faced by persons with disabilities in accessing sports and recreation, the Dutch Knowledge Centre for Sport & Physical Activity (KCSA) has developed a sustainable, two-way system that bridges the gap between national policy and local practice. This initiative stimulates regional communities to create an inclusive sports infrastructure.The Netherlands has a multi-level governance system, with national policies set by the government, provinces overseeing regional implementation, and municipalities responsible for local execution. Within this structure, KCSA has trained ‘knowledge holders’ in every province, who are tasked with supporting stakeholders (e.g. coaches and healthcare professionals) when they face local challenges. By doing so, they create regional networks, while simultaneously collecting insights from the field. This enables a feedback loop to the Ministry of Health, Welfare and Sport, ensuring policies are grounded by practical realities.This infrastructure also supports the implementation of national policies, such as the development of a model policy for adaptive sports equipment under the Social Support Act. Given that municipalities are not mandated to adopt such policies, knowledge holders play a key role that goes beyond informing municipalities. They actively engage them by highlighting the importance of inclusive sports policies, advocating for structural improvements. Aligned with Sustainable Development Goal 10, ‘Reduce inequality within and among countries’, this initiative builds inclusive networks that promote equal opportunities in sports and recreation for persons with disabilities. By empowering knowledge holders, the initiative creates a healthy and sustainable sports structure that serves persons with disabilities.